2005
DOI: 10.1111/j.1547-5069.2005.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Models of Supervision on Selected Outcomes

Abstract: Supervision ratings before and after the interventions differed significantly in the total sample, but not by district. In the district with the MM model, care for people with chronic diseases improved significantly, but other measures did not. The supervision training had some influence, but more measures of effectiveness of supervision training are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…For example, in India, supervisors did not like participatory problem solving as they preferred the status of their position in a hierarchical system (51). In terms of formal quality assurance tools, supervisors can understand and use tools such as flow diagrams (86), brain storming for prioritization, and matrix analysis for selection of solutions (87); however, a single training on quality improvement may not be sufficient to garner change (29). Less formal tools such as self-assessments with action plans may be feasible solutions for private providers in remote locations or small practices (82).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in India, supervisors did not like participatory problem solving as they preferred the status of their position in a hierarchical system (51). In terms of formal quality assurance tools, supervisors can understand and use tools such as flow diagrams (86), brain storming for prioritization, and matrix analysis for selection of solutions (87); however, a single training on quality improvement may not be sufficient to garner change (29). Less formal tools such as self-assessments with action plans may be feasible solutions for private providers in remote locations or small practices (82).…”
Section: Resultsmentioning
confidence: 99%
“…Supervisors of nurses in South Africa received a one-time training session in one of the two models: the Modified Matrix model focused on the supervisor–supervisee relationship, the institutional and client environment, and the tasks and functions of the supervisor and supervisee, while the Centre for Health and Social Studies model focused on training supervisors in understanding and practicing the principles of primary health care and continuous quality improvement. Neither intervention had significant impact on outcomes, including job satisfaction, patient satisfaction, or quality of hypertension or diabetes care (29); however, the impact of these models may have been limited by not taking a more comprehensive approach. In Zimbabwe, pharmacists and pharmacy technicians without supervision experience were trained to supervise primary health care workers in a three-arm randomized control trial comparing interventions to improve stock management and adherence to treatment guidelines to each other and to a control (88).…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa, nurses were found to be generally dissatisfied with their jobs and remuneration, poor working conditions and organizational climate were strong predictors [27,28,46]. A study from Rwanda revealed that factors such as remuneration, opportunities for growth, working conditions, recognition, rewards, appreciation, and benefits and allowances could contribute to nurses' levels of motivation [47].…”
Section: Factors Affecting Job Satisfactionmentioning
confidence: 99%
“…However, analysis of outcomes of patients assigned to a third arm of the study, who were treated in a problem-solving therapy without supervision, suggested that supervision of either kind improved patient outcome. Similarly, Uys, Minnaar, Simpson and Reid (2005) found that the two supervision approaches that they compared (i.e. a developmental model, and one based on Holloway's 1995 matrix model) both produced similarly significantly improved supervisee ratings of supervision.…”
Section: Introductionmentioning
confidence: 86%